One-Year Safety of Olodaterol Once Daily via Respimat® in Patients with GOLD 2–4 Chronic Obstructive Pulmonary Disease: Results of a Pre-Specified Pooled Analysis. (3rd September 2015) - McGarvey, Lorcan; Niewoehner, Dennis; Magder, Sheldon; Sachs, Paul; Tetzlaff, Kay; Hamilton, Alan; Korducki, Lawrence; Bothner, Ulrich; Vogelmeier, Claus; Koch, Andrea; Ferguson, Gary T.
Abstract: The novel long-actingβ 2 -agonist olodaterol demonstrated an acceptable safety profile in short-term phase II clinical studies. This analysis of four randomized, double-blind, placebo-controlled, parallel-group, phase III studies (1222.11, NCT00782210; 1222.12, NCT00782509; 1222.13, NCT00793624; 1222.14, NCT00796653) evaluated the long-term safety of olodaterol once daily (QD) in a large cohort of patients with moderate to very severe (Global initiative for chronic Obstructive Lung Disease 2–4) chronic obstructive pulmonary disease (COPD). The studies compared olodaterol (5 or 10 μg) QD via Respimat®, formoterol 12 μg twice daily (BID) via Aerolizer® (1222.13 and 1222.14), and placebo for 48 weeks. Patients continued receiving background maintenance therapy, with ∼60% receiving concomitant cardiovascular therapy and 25% having a history of concomitant cardiac disease. Pre-specified analyses of pooled data assessed the adverse events (AEs) and serious AEs in the whole population, and in subgroups with cardiac disease, along with in-depth electrocardiogram and Holter monitoring. In total, 3104 patients were included in the safety analysis: 876 received olodaterol 5 μg, 883 received olodaterol 10 μg, 885 received placebos, and 460 received formoterol 12 μg BID. Overall incidence of on-treatment AEs (71.2%), serious AEs (16.1%), and deaths (1.7%) were balanced across treatment groups. Respiratory and cardiovascular AEs, including major adverse cardiac events, were reported at similar frequencies in placebo and active treatment groups. The safety profiles of both olodaterol 5 μg (marketed and registered dose) and 10 μg QD delivered via Respimat® are comparable to placebo and formoterol BID in this population, with no safety signals identified.